Kyai dan Politik : Peranan K.H. Mahfudz Ridwan dalam Partai Kebangkitan Bangsa 1998-2008: Ulema and Politics: The Role of K.H. Mahfudz Ridwan in the National Awakening Party 1998-2008 - Kadomi, Muhammad Fairus (Journal of Islamic History, 2022)
The focus of the discussion in this research is about Kyai and Politics, the study of the role of K.H. Mahfudz Ridwan in the PKB. This article reveals how a kyai figure who has a role or contribution in a political party affiliated with an Islamic group. The method used in this research is the historical method. The dynamics of politics from the new order to the reformation era are historically important because the faucet of democracy will be opened, after which in the reform era several major parties emerged that characterize democracy in Indonesia. There are more and more Islamic political parties in the reform era and the contact of the kyai with politics is visible. K.H. Mahfudz Ridwan who is a kyai looks active in the social and political world. K.H. Mahfudz Ridwan is a figure who plays an active role in NU mass organizations, Islamic boarding schools, the world of social empowerment by being proven to have founded the Edi Mancoro Islamic Boarding School, Gedangan Forum, Desaku Maju Foundation and was involved in social politics during the Old Order until the reform era. The role of K.H. Mahfudz Ridwan appeared in the context of the formation of the PKB party, namely as an internal and external initiator of the PKB party.